PERSEPSI MAHASISWA TERHADAP PRAKTIKUM DARING MATA KULIAH KIMIA ANALISIS - Romadhiyana Kisno Saputri; Akhmad Al-Bari (Jurnal Educatio FKIP UNMA, 2020)
During the COVID-19 pandemic period, every education unit requires an online learning process, not only for theoretical courses, but also for practical courses, including analytical chemistry practicum courses. Student perceptions of online lectures can help students in implementing the process lectures during the Covid 19 pandemic, because a good and correct lecture will help students improve their understanding and knowledge of students. This study aims to find out students perception about online practicum in analytical chemistry. This research is a qualitative descriptive study. The sample was taken using simple random sampling consisted of 45 students. Data were obtained using questionnaires and in-depth interviews. Student perceptions were seen from three aspects, teaching and learning process, the ability of lecturers, facilities and infrastructure which were assessed using a likert scale. The data analysis by qualitative analysis, consisting of data collection, data reduction, data presentation, and conclusion drawing. Student perceptions in all aspects have a mean of 64.95% so that students 'perceptions of online practicum in analytical chemistry are positive. Students' perceptions of teaching and learning aspects have a value of 69.57% which indicates a positive perception, on aspects of lecturer competence have a value. 77.90% which shows a positive perception of the infrastructure aspect has a value of 47.39% which indicates a positive perception. Keywords: students perceptions; online practicum; Analytic Chemistry